(untitled) (Journal of Universal Science Research, 2023)
The linguistic picture of the world reflects the national picture of the world and can be identified in linguistic units of different levels. The study of the reflection of the linguistic picture of the world in literary texts and proverbs, to which we have paid the main attention in this work, makes it possible to identify the specifics of the cultural picture of the world. Texts are true keepers and translators of culture. The semantic composition of the concept includes all pragmatic linguistic sign information related to its expressive and illocutionary functions. Another component of the semantics of a language concept is the cognitive memory of a word - the semantic characteristics of a language sign associated with its original purpose and the system of spiritual values of native speakers. However, conceptually the most significant here is the cultural-ethnic component, which determines the specifics of the semantics of natural language units and reflects the “linguistic picture of the world” of its speakers. The concept is correlated with the plan of expression of the lexico-semantic paradigm. Semantic field, or paradigmatic lexico-semantic a group unites words connected by semantic relations, i.e. relations of signs to what signs mean, to objects of reality and concepts about them.